S113 The radiological route to diagnosis of lung cancer patients. (December 2018) - Aslam, R; Kennedy, MPT; Bhartia, B; Shinkins, B; Neal, RD; Callister, MEJ
Abstract : Introduction and objectives: The route-to-diagnosis of lung cancer patients has been well studied, with those diagnosed following emergency presentation shown to have worse outcomes. Much less is known about patient outcomes according to the imaging that leads to their diagnosis, and the context in which this was ordered. We therefore sought to describe 'Radiological Routes to Diagnosis' (RRTD), and assess the frequency of these routes, and the outcomes of cancer patients according to these categories. Methods: In the absence of any previous categorisation that we were aware of, we defined 7 RRTDs for patients diagnosed with lung cancer in Leeds Teaching Hospitals in 2013 (n=570). Lung cancer outcomes were assessed between categories. Abnormal CXR for symptoms as defined by NICE Lung Cancer guidelines Abnormal CXR for any other reason CT thorax due to NICE Lung Cancer symptoms despite normal/benign/no prior CXR CT Pulmonary Angiogram (CTPA) Incidental finding on other imaging modality Patient undergoing CXR surveillance following a previously abnormal CXR Patient undergoing CT surveillance following a previously abnormal CT scan Results: By far the commonest RRTD was referral for CXR following NICE symptom (56%). Numbers by other routes were as follows route 2 (6%), route 3 (5%), route 4 (2%), route 5 (13%), route 6 (8%), and route 7 (9%). Survival curves by RRTD are shown in figure 1. Patients diagnosed following CT surveillance had better overall survival rate compared to other groups (Hazard ratio=0.56 [95% CI: 0.42–0.73]) reflecting less metastatic disease (8% cases), and a greater chance of undergoing radical treatment (70%). Similarly patients undergoing interval CXR also had improved survival (Hazard ratio=0.73 [95% CI: 0.54–0.98]). However, no indication of a difference in survival or other outcomes were seen between any of the other 5 RRTDs. Conclusion: Whilst improved outcomes for patients diagnosed following CT surveillance are to be expected, it is notable that most other RRTDs have similarly poor outcomes.